La matérialisation de la transition énergétique dans les milieux urbains denses. Le cas du projet urbain Nanterre Cœur Université - Meriam Bechir (Développement Durable et Territoires)
Through the story of the energy and spatial design of the Nanterre Coeur Université urban developpement project, we will show that the ambitious energy objectives of sustainable projects can strongly constrain the design of projects and, in some cases, encourage a multiplication of the energy artifacts mobilized. Energy design thus involves various negotiations between public and private actors. These negotiations can, in some cases, question the energy objectives and technical choices even at advanced stages of the design. Finally, we will show that the integration of energy artifacts has a strong impact on the spatiality of projects, mainly by reducing net useable areas and by creating competition between uses.